2011
DOI: 10.1111/j.1472-765x.2011.03063.x
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the denitrification pathway influences cell growth and magnetosome formation in Magnetospirillum magneticum AMB-1

Abstract: Aims:  Intracellular magnetosome synthesis in magnetotactic bacteria has been proposed to be a process involving functions of a variety of proteins. To learn more about the genetic control that is involved in magnetosome formation, nonmagnetic mutants are screened and characterized. Methods and Results:  Conjugation‐mediated transposon mutagenesis was applied to screen for nonmagnetic mutants of Magnetospirillum magneticum AMB‐1 that were unable to respond to the magnetic field. A mutant strain with disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In contrast to Nap, NirS is not absolutely required for anaerobic respiration, which substantiates the previous finding that nitrate reduction catalyzed by Nap is the primary energy-generating process in denitrification of MSR-1 (13). In M. magneticum, a similar phenotype (poor an-aerobic growth, impaired magnetite synthesis) was observed upon concomitant interruption of norB and nirS (amb1395) (37). Since an additional nirS homolog (amb4165) is present in the M. magneticum genome, the results of Wang et al (37) imply that Amb1395 might be the main nitrite reductase, while Amb4165 has no significant function in denitrification and magnetite synthesis.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In contrast to Nap, NirS is not absolutely required for anaerobic respiration, which substantiates the previous finding that nitrate reduction catalyzed by Nap is the primary energy-generating process in denitrification of MSR-1 (13). In M. magneticum, a similar phenotype (poor an-aerobic growth, impaired magnetite synthesis) was observed upon concomitant interruption of norB and nirS (amb1395) (37). Since an additional nirS homolog (amb4165) is present in the M. magneticum genome, the results of Wang et al (37) imply that Amb1395 might be the main nitrite reductase, while Amb4165 has no significant function in denitrification and magnetite synthesis.…”
Section: Discussionsupporting
confidence: 72%
“…In M. magneticum, a similar phenotype (poor an-aerobic growth, impaired magnetite synthesis) was observed upon concomitant interruption of norB and nirS (amb1395) (37). Since an additional nirS homolog (amb4165) is present in the M. magneticum genome, the results of Wang et al (37) imply that Amb1395 might be the main nitrite reductase, while Amb4165 has no significant function in denitrification and magnetite synthesis. However, in our experiments, both amb1395 and amb4165 from M. magneticum when placed under the control of the nirS promoter region from MSR-1 were able to fully restore WT-like growth and magnetosome formation in the MSR-1 ⌬nirS mutant, indicating that the speculated lack of amb4165 function might be due to transcriptional inactivity under the test conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Whereas deletion of nosZ only had a weak effect on anaerobic growth and biomineralization, we were unable to detect any growth in our ⌬norCB mutant of MSR-1 under anaerobic and microaerobic conditions in the presence of nitrate, probably due to the toxicity of the accumulated intermediate nitric oxide, since growth could be rescued by additional deletion of nirS in the ⌬norCB background (Y. Li and D. Schüler, unpublished data). In contrast, in a previous study Wang and colleagues reported some growth for an AMB-1 ⌬norB mutant under anaerobic conditions (61). The discrepancy between nor mutants of MSR-1 (no growth) and AMB-1 (poor growth) might be due to different genotypes, since in the AMB-1 mutant only norB (located downstream of norC) was interrupted by transposon insertion, thereby possibly retaining some residual activity of the nitric oxide reductase enzyme.…”
Section: Discussionmentioning
confidence: 55%
“…Later, a soluble periplasmic nitrate reductase implicated in magnetite synthesis was purified from MS-1 (56). Wang et al recently interrupted a gene (norB) for nitric oxide reductase in AMB-1 by transposon insertion and found that shorter magnetosome chains were produced under anaerobic conditions (61). However, except for this single study, no genetic evidence has been available for these possible functions in vivo so far, and the exact interrelation of these two pathways as well as the redox process governing magnetite biomineralization has largely remained unclear.…”
mentioning
confidence: 99%
“…It is interesting to note that these latter elements are known to be cofactors of metalloenzymes (32) that are essential for bacterial growth and metabolism. Molybdenum is indeed required for nitrate reductase enzymatic activity, which has been reported in AMB-1 and other MTB strains (33,34). The nitrate reductase reduces nitrate for cell respiration and is also necessary for the magnetite biomineralization in strains MSR-1 and AMB-1 (33, 34).…”
Section: Resultsmentioning
confidence: 96%